QUANTITATIVE AUTORADIOGRAPHIC STUDY OF LABELED RNA IN RABBIT OPTIC NERVE AFTER INTRAOCULAR INJECTION OF [(3)H]URIDINE - Gambetti, Pierluigi (The Rockefeller University Press, 1973)
The distribution of labeled RNA in the optic nerve of the rabbit was studied by quantitative ultrastructural autoradiography after the intraocular injection of [(3)H]uridine. The highest density of silver grains related to [(3)H]RNA (27–40 grains/100 µm(2)) was found in glial cell perikarya; a slightly lower density was present in the glial nuclei (19–20 grains/100 µm(2)). Axons (4–5 grains/100 µm(2)) and myelin (2–3 grains/100 µm(2)) had the lowest grain densities. 74–83% of all counted grains were located outside the axons. By comparing the grain density distribution over the axon with that expected in the case of an exclusive labeling of the surrounding myelin and glial cell processes, it was concluded that the axons contained a number of grains representing [(3)H]RNA significantly higher than that expected to scatter from myelin and glial processes. Most of these grains were concentrated at the periphery of the axon and were not related to axonal mitochondria.